Sistem Informasi E-Learning Pada SMKN 1 Nangaroro Menggunakan Metode Unified Modelling Language (Uml) - Walternus Nggeta Wawo; Yoseph D. Da Yen Khwuta; Elvira Esperanza Sala (Teknik Komputer Politeknik Negeri Sriwijaya, 2023)
Abstract The problem that has occurred at SMKN 1 Nangaroro so far is the difficulty of teachers to provide material to their students due to the increasing covid-19 pandemic which causes the transfer of knowledge to be late if the meeting does not occur. The purpose of this study was to design an e-learning information system at SMKN 1 Nangaroro. The use of e-learning information systems can help teachers and students in carrying out the teaching and learning process. The website-based e-learning information system uses a unified modelling language method to facilitate the learning process and can help agencies to convey information widely.The results of the e-learning information system using the unified modelling language method can improve the quality of education because the learning process between teachers and students can be done online. This website-based e-learning system is already functioning properly, with the evidence of blackbox testing which states success, which shows that the system is acceptable for use at SMKN 1 NANGARORO. In the next development, this e-learning system can be added to the student attendance feature. Not only that, because it is website-based, it can be converted into an android application so that you don't have to type in the address / url of this e-learning system Keywords— E-lerning, Information System, UML, Black Box, Waterfall